GENETIC SPECIES OF DAM LAKES IN CENTRAL ASIA AND PROBLEMS OF THEIR CLASSIFICATION (Scientific journal of the Fergana State University, 2024)
Dam lakes, which are common in mountainous regions of the globe, are one of the main sources of flood risk. Studying them, preventing the risk of floods that can arise for various reasons, predicting them and assessing the level of danger is one of the important tasks facing limnologists today. To do this, first of all, it is desirable to study the genetic types of dammed lakes. For this purpose, this article describes the genetic types of dammed lakes in the mountainous regions of Central Asia.